2021
DOI: 10.1002/trc2.12213
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of individual research results at federally funded Alzheimer's Disease Research Centers

Abstract: Introduction This study describes practices for disclosing individual research results to participants in Alzheimer's disease research. Methods An online survey of clinical core leaders at National Institutes of Health‐funded Alzheimer's Disease Research Centers in the United States (response rate: 30/31, 97%) examined return of results practices across nine different types of research results. Results Most centers had returned consensus rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Surveys conducted prior to the approval of amyloid PET scans for clinical use found that a majority of dementia specialists planned to use them to identify asymptomatic persons at risk for AD dementia, 38 while others would be reluctant to share results for fear of negative psychosocial outcomes 39 . The limited data available suggest that actual practices of disclosure in research settings may vary widely in what is disclosed and how 3 . Patterns of disclosure may similarly diverge in clinical contexts.…”
Section: What Is Known About Disclosure In Preclinical Ad?mentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys conducted prior to the approval of amyloid PET scans for clinical use found that a majority of dementia specialists planned to use them to identify asymptomatic persons at risk for AD dementia, 38 while others would be reluctant to share results for fear of negative psychosocial outcomes 39 . The limited data available suggest that actual practices of disclosure in research settings may vary widely in what is disclosed and how 3 . Patterns of disclosure may similarly diverge in clinical contexts.…”
Section: What Is Known About Disclosure In Preclinical Ad?mentioning
confidence: 99%
“…Preclinical biomarker testing can identify individuals for clinical trials, and ultimately may allow earlier diagnosis and initiation of targeted pharmacologic therapies. Amyloid biomarkers such as positron emission tomography (PET) imaging are increasingly being disclosed to cognitively unimpaired participants in research trials 3,4 . Disclosure of preclinical biomarkers is currently not recommended for clinical practice 5 .…”
Section: Introductionmentioning
confidence: 99%
“…While explanations of study procedures are routinely offered during informed consent, the longitudinal nature of ADRD cohort research warrants ongoing explanations of procedures, especially those that may be perceived as burdensome (eg, lumbar puncture and neuropsychological testing). Yet, with the exception of articles on research test results disclosure, the literature on communicating with ADRD research participants focuses almost exclusively on pre-enrollment explanations of the research 9. The ADRCs in this study invite participants to annual events to honor their contributions and share results, but more may be needed to communicate with participants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research centers vary widely in their practice of AD research test results disclosure to study participants, with biomarker data less commonly disclosed than cognitive test results (31). Researchers have raised concerns regarding the potential psychological impact of disclosure, particularly for those receiving news of increased AD risk in the absence of a broadly available disease-modifying treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have raised concerns regarding the potential psychological impact of disclosure, particularly for those receiving news of increased AD risk in the absence of a broadly available disease-modifying treatment. However, some studies also suggest that the risk of psychological harm is relatively low, especially with the provision of genetic counseling (30, 31, 33, 34), and efforts are underway to optimize disclosure protocols for dementia risks to research participants (32). While our findings indicate some support for sharing research test results with study participants, they also point to emerging views about the type of data participants want disclosed, such as both normal and abnormal results as well as non-genetic test results.…”
Section: Discussionmentioning
confidence: 99%